Periodontitis, assessed using periodontal treatment as a surrogate marker, has no association with a first myocardial infarction in a Swedish population. Issue 12 (27th March 2021) - Nordendahl, Eva; Fored, Michael; Kjellström, Barbro; Ekbom, Anders; Norhammar, Anna; Gustafsson, Anders
Abstract: Background: Periodontitis is suggested to be associated with a risk of cardiovascular events. Using periodontal treatment recorded in Swedish national registries as a surrogate marker, we aimed to investigate whether periodontitis was associated with a first myocardial infarction. Methods: This nationwide case‐control study, with data from national registries, involved 51, 880 individuals with a first myocardial infarction in 2011 to 2013 (index date) and 246, 978 controls matched 5:1 for age, gender, and geographic area. Periodontal treatment in the 3 years preceding the index date was classified as (1) no dental treatment, (2) no periodontal treatment, (3) one or more supragingival curettages, or (4) one or more treatments with scaling/root planing and/or periodontal surgery. Annual frequencies of treatment with scaling/root planing and/or periodontal surgery were also calculated. In all analyses, conditional logistic regression analyses estimated ORs for myocardial infarction with 95% CIs, adjusted for matched variables, income, education, and diabetes. Results: Although fewer cases than controls received treatment with scaling/root planing and/or periodontal surgery (19.2% versus 19.8%, P < 0.001), annual frequencies for cases were higher. We found no association of scaling/root planing and/or periodontal surgery with a first myocardial infarction (OR = 1.02; 95% CI: 1.00, 1.05). We did observe a non‐significant trend, however, between risk of a first myocardial infarction and a high frequency of scaling/root planing and/or periodontal surgery (OR 1.14; 95% CI: 1.00, 1.29). Conclusion: In the contemporary Swedish nationwide setting, no association between a first myocardial infarction and periodontitis, assessed as periodontal treatment, was found.